Uso dos dados da missão GRACE para estudo dos eventos de estiagem na bacia hidrográfica do Rio Uruguai, no período entre 2003 a 2015 - Moraes, Indiara Bruna Costa Moura (2019)
Cities located in the Uruguay River Basin have been hit periodically by droughts that have caused major economic damage to the region. There is a wide range of flow rates, since the occurrence of major droughts, affecting human and animal supplies, experiencing losses in Primary Sector output and indirect effects on other sectors, and also, the increase in the cost of living of the population. The objective of this research is to analyze variations in total water storage by the GRACE Mission (Gravity Recovery & Climate Experiment) in the Uruguay Basin Hydrographic Region, allowing a better understanding of drought and behavior along rivers, mainly in the low coverage areas of the river stations between 2003 and 2015. In this research, masks of CSR GRACE RL05 solutions were used to obtain the Equivalent water thickness in cm. The time series of the GRACE mission were compared with the wells, where the weighted average was applied, considering all wells in the region, based on the area of influence of each well determined by the Thiessen polygons. A priori, fluviometric stations were selected in the same municipalities that monitor groundwater wells. Monthly averages were calculated on the water quota information obtained from the readings of the rulers and compared the behavior of water levels with EqW and the levels of underground wells. The records of droughts obtained from decrees of emergency situation and state of public calamity were divided into numbers of municipalities affected per year and number of events per year, as there are municipalities with more than one event per year. And the normalized vegetation index obtained from the MODIS sensor during the study period was used to correlate with the EqW obtained by the mascon solutions of the GRACE mission. To verify the correlation between the EqWs and the normalized vegetation indices, a geographically weighted regression was performed, between the EqW values and the normalized vegetation indices, obtaining the value of R² = 0.979. The methodology used was presented as an option for the evaluation of drought events in the Uruguay River Basin. There was a direct relationship between the increase in emergency decrees or state of emergency with the decrease in EqW levels in the aforementioned area, allowing note that EqW level of decline begins months before the decrees, realizing that the drought is the path from 1 year to 6 months before and plan economically for such an event because the basin takes about four months to recover from the great peak of the drought. As the time series of the GRACE mission is still small for hydrological studies, suggest a regression of data to assist in these studies and also predict the behavior in EqW in the future, helping in the management of water resources.